Class Struggle Representation by Phineas Taylor Barnum in the Greatest Showman Movie - Rianti, Rianti; Bahar, Bahar; Basri, Basri (Universitas Muhammadiyah Gorontalo, 2024)
The Greatest Showman tells the story of Barnum's journey to realize his dream of establishing the Barnum & Bailey Circus, a large circus featuring people with physical uniqueness and extraordinary talents. This study aims to analyze how the class struggle depicted by PT Barnum as the main character to achieve success, as well as the forms of power carried out by the main character in the film The Greatest Showman. In this study, the researcher used a qualitative descriptive research method using the analysis of the French & Raven (1959) power theory. Data collection techniques were carried out by means of observation and literature study. Based on the research that has been done, the researcher concludes that this film shows many things to become a good leader and be able to have a big impact on society. We are all leaders in our lives. So, this film gives us many things that we can learn to have a better life.